Modern view of the solar wind from micro to macro scales. (November 2020) - Petrukovich, A A; Malova, H V; Popov, V Yu; Maiewski, E V; Izmodenov, V V; Katushkina, O A; Vinogradov, A A; Riazantseva, MO; Rakhmanova, L S; Podladchikova, T V; Zastenker, G N; Yermolaev, Yu I; et al.
Abstract: Solar wind — a plasma stream flowing out of the solar corona — is interesting both as a carrier of solar activity and as an example of a collisionless plasma. We present the main results of Russian studies in recent years. The original MHD model allows interpreting the bifurcation of the heliospheric current sheet during maximum activity years as occurring due to the quadrupole component of the heliomagnetic field. On a scale of the order of millions of kilometers, the solar wind consists of transient solar formations. On these scales, one of the basic geomagnetic forecast problems has been solved: it was shown that the interplanetary magnetic field can be assumed stable at times of about three hours. At small scales (hundreds to thousands of kilometers), local structures are formed that can be regarded, both individually and statistically, as turbulent cascades .